ChemInform Abstract: Asymmetric Hydrogenation of Pyridinium Salts with an Iridium Phosphole Catalyst. Issue 16 (April 2015) - Chang, Mingxin; Huang, Yuhua; Liu, Shaodong; Chen, Yonggang; Krska, Shane W.; Davies, Ian W.; Zhang, Xumu
Abstract Chiral piperidines are easily prepared by Ir‐catalyzed asymmetric hydrogenation of alkylpyridinium salts.